Functionalized carbon nanotubes for adsorptive removal of water pollutants - Lee, Kian Mun; Wong, Christelle Pau Ping; Tan, Tong Ling; Lai, Chin Wei (Elsevier, 2018)
Today, clean water shortages will cause the next great global crisis. As such, several conventional water treatment methods, including physical, chemical, and biological treatments have been applied before discharge to the environment. Nevertheless, these conventional water treatments exhibited several drawbacks, including small wastewater flow rate, expensive in production, high working pressure to push the wastewater flow, diffusion limitation and inability to reduce dissolved solid content. Today, carbon nanotubes (CNTs) appear to be one of the most promising technologies for water remediation. CNTs have attracted much attention from scientist and researcher community due to their unique properties, including its high catalytic, adsorption, transport and electrical properties. This paper presents recent achievements on chemical modification methods for CNTs using different approaches (fluorination, cycloaddition, reaction with diazonium salt, oxidation and radical polymerization) for enhancing the CNTs’ solubility and reactivity. Besides, the role of CNTs on water remediation platform will be discussed.